ANALYSIS OF SPATIAL DISTRIBUTION CHARACTERISTICS AND INFLUENCING FACTORS OF RESIDENTIAL LAND PRICE IN CHINA - BASED ON MACRO-SCALE - Oliver Valentine Eboy; Ma Hong (Journal of Islamic, Social, Economics and Development, 2023)
Based on the macro-scale, taking 27 provincial capitals and 4 municipalities in China in 2010 and 2020 as the research objects, the spatial distribution and influencing factors of urban residential land price were analyzed by using the exploratory spatial data analysis method and regression analysis model. The results show that: (1) The urban residential land price showed the distribution characteristics of "high in the east and low in the west", and the residential land price as a whole shows a trend that the attenuation rate around the high-value center decreases with the increase of distance. (2) In 2020, the high-value centers of the residential land price changed from coastal areas to inland areas, and the residential land price will develop from a single high-value center in coastal areas to a double high-value center. (3) The economic development and living standard of residents in the study area play a major role in the residential land price. However, from the perspective of specific factors, the influencing factors of residential land price in 2020 are also affected by the epidemic situation, with the decrease in foreign exchange and the decrease of the influence of foreign investment on the residential land price.